Characterization and performance study of commercially available solid oxide cell stacks for an autonomous system. (1st January 2020) - Preininger, Michael; Stoeckl, Bernhard; Subotić, Vanja; Hochenauer, Christoph
Highlights: Single cell measurements showed partially high disparities of the individual layers. A high utilization/conversion of 80% is applied in a transient operating procedure. The co-flow configuration showed a more homogeneous temperature distribution. Slightly exothermic operation balances the endothermic electrolysis reactions. Abstract: The solid oxide cell (SOC) is a key technology for a combined generation of electricity, heat and valuable fuels in a highly efficient manner. By integrating a reversible SOC module in a compact unit, an autonomous reversible system may be realized. In order to obtain more information on the durability and reliability of SOCs, relevant stacks from different manufacturer are operated in both fuel cell and electrolysis mode under realistic operating conditions. The stacks are at relevant research and operational testing level. Thus, they are subjected to similar and comparable conditions while remain within given system boundaries. The results provide an insight for assessing the possibilities with respect to practical application under full load in fuel cell mode and efficient operation with a constantly high reactant conversion of 80% in both H2 O- and co-electrolysis. The resulting operating maps can be considered and used for model evaluations and system designs. Further suggestions and proposals for improvements to be made are related to the thermal layout and the gas flow management of the experimental design in order to obtain more uniform cell performances.